Recuerdos matodológicos: el taller y la investigación etnográfica - Pilar Riaño Alcalá (Estudios sobre las Culturas Contemporáneas)
Tliis ardcle presents an etlinographic exploration of die recollection workshops wliich took place during die field work for a study on collecdve memory of urban dwellers in die cides of Medellin and Bogota, Colombia. The ardcle develops a cliaracterization of die workshop as a group and interacdve method diat diat locates itself in dme and space and which is framed by a reladonal dynamic tliat overflows the subjectinvestigator relation.